2021
DOI: 10.4049/jimmunol.2100719
|View full text |Cite
|
Sign up to set email alerts
|

The Sympathetic Nervous System Modulates Cancer Vaccine Activity through Monocyte-Derived Cells

Abstract: The sympathetic nervous system (SNS) is an important regulator of immune cell function during homeostasis and states of inflammation. Recently, the SNS has been found to bolster tumor growth and impair the development of antitumor immunity. However, it is unclear whether the SNS can modulate APC function. Here, we investigated the effects of SNS signaling in murine monocyte-derived macrophages (moMФ) and dendritic cells (DCs) and further combined the nonspecific β-blocker propranolol with a peptide cancer vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…8 In addition, propranolol administration together with tumour vaccines enhanced vaccine immunity and the accumulation of T cells within tumour tissues. [51][52][53][54] Similar immune enhancing effects were observed when propranolol was co-administered with ICI (immune checkpoint inhibitor) immunotherapy. 4,[26][27][28]55 Importantly, studies have also demonstrated that pharmacologic activation of the SNS pathway, using beta agonists such as isoproterenol, stimulated tumour growth associated with greater mobilisation of MDSC from bone marrow and accumulation in tumour tissues.…”
Section: Clinical Applications Of β-Blockade To Cancer Immunotherapymentioning
confidence: 64%
See 1 more Smart Citation
“…8 In addition, propranolol administration together with tumour vaccines enhanced vaccine immunity and the accumulation of T cells within tumour tissues. [51][52][53][54] Similar immune enhancing effects were observed when propranolol was co-administered with ICI (immune checkpoint inhibitor) immunotherapy. 4,[26][27][28]55 Importantly, studies have also demonstrated that pharmacologic activation of the SNS pathway, using beta agonists such as isoproterenol, stimulated tumour growth associated with greater mobilisation of MDSC from bone marrow and accumulation in tumour tissues.…”
Section: Clinical Applications Of β-Blockade To Cancer Immunotherapymentioning
confidence: 64%
“…For example, in one study propranolol treatment reversed the recruitment of MDSC into tumour and lymphoid tissues, slowed the growth of subcutaneous tumours and blocked tumour metastases 8 . In addition, propranolol administration together with tumour vaccines enhanced vaccine immunity and the accumulation of T cells within tumour tissues 51–54 . Similar immune enhancing effects were observed when propranolol was co‐administered with ICI (immune checkpoint inhibitor) immunotherapy 4,26–28,55 .…”
Section: Clinical Applications Of β‐Blockade To Cancer Immunotherapymentioning
confidence: 91%